Synchronization of repolarization after cardiac resynchronization therapy: time course and relation to reverse remodeling. (19th May 2022) - Prinzen, F; Verzaal, NJ; Van Deursen, CJM; Pezzuto, S; Wecke, L; Vernooy, K; Delhaas, T; Auricchio, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The changes in ventricular repolarization after cardiac resynchronization therapy (CRT) are poorly understood. Objective: Address this knowledge gap using a multimodality approach including electrocardiographic and echocardiographic measurements in patients and patient-specific computational modeling. Methods: In a cohort of consecutive CRT patients, electrocardiographic and echocardiographic measurements were performed before and at various intervals after CRT, both during CRT-ON and temporary CRT-OFF. T-wave area was calculated from vectorcardiograms, reconstructed from the 12-lead ECG. Computer simulations were performed using a patient-specific eikonal model of cardiac activation with spatially varying action potential duration (APD) and repolarization rate, based on a patient's ECG and MRI-based chest and cardiac anatomy. Results: In 33 patients T-wave area during CRT-OFF doubled within 5 days of CRT (left figure) while other repolarization markers like QT-interval and peak-to-end T-wave interval hardly changed. Patients with T-wave area increase above the median increase showed a significantly larger increase in left ventricular ejection fraction than those with smaller T-wave area increase (+11±8% vs. +6±6%, respectively; p<0.05, n=76). Computer simulations (figure, right) show the sequence of depolarization and repolarization before CRT, obtained by the patient-specific model (BL LBBB) and following Acute CRT. Repolarization after chronic CRT-OFF was obtained by matching the measured CRT-OFF ECG with that provided by the model. The best match was obtained by changes in APD following chronic CRT that are opposite to the change in CRT-induced activation time. Such APD changes were associated with a reduction in right and left ventricular dispersion in repolarization during chronic CRT-ON compared with acute CRT-ON. Conclusions: T-wave area during CRT-OFF is a sensitive marker for adaptations in ventricular repolarization after CRT that are related to CRT-induced reverse remodeling and may involve an inverse relation between activation time and APD, coinciding with lower right and left ventricular dispersion of repolarization and with larger increases in LV ejection fraction during chronic CRT.